Perbandingan Hasil Data Gravitasi Permukaan Tanah dan Satelit GGMPlus (Studi Kasus: Cekungan Kalibening) - I Putu Arix Putra Wiguna; Mohammad Syamsu Rosid; Frilla Renty Tama Saputra (Jurnal Penelitian Pendidikan IPA, 2024)
As technology develops, many satellite gravity data with world coverage and high resolution have become available, one of which is GGMPlus. However, the quality of the resulting satellite gravity data is still doubtful, because the GGMPlus satellite data is the result of calculations. This research will compare satellite data with land surface data in the Kalibening Basin area to see the precision and correlation of satellite data with land surface data. Land surface data was obtained from field measurements using Scintrex CG-5 with a grid between stations of 500-1000m and GGMPlus satellite gravity data with a distance between points of 600m. The results obtained show that the residual anomaly maps have many similarities, while the regional anomalies provide quite significant differences between the two data. The slicing results show a density contrast that is similar to the two data and matches the geological boundaries of the Kalibening Basin. Based on the results obtained, GGMPlus data can be an alternative to fill the gaps in field data or as supporting data in disaster mitigation and exploration in general. The correlation between land surface data and GGMPlus is quite rational with a value of R2 = 0.95 and RMSE = 6.89mGal.